2018
DOI: 10.1248/cpb.c18-00380
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Synergism and Anti-biofilm Activity of Quercetin–Pivaloxymethyl Conjugate against <i>Staphylococcus aureus</i> and <i>Enterococcus</i> Species

Abstract: Upon single treatment against Staphylococus aureus, quercetin-pivaloxymethyl conjugate (Q-POM) had antibacterial activities with minimum inhibitory concentrations (MICs) of 16-32 mg/L. Q-POM showed MIC of 32 mg/L against vancomycin-resistant Enterococcus faceium (VRE), which is remarkably lower than other antibiotics investigated (≥256 mg/L). Under sub-MIC concentrations, Q-POM potentiated the activity of ampicillin, cefepime, and vancomycin against S. aureus and Enterococcus (including highly resistant strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…Quercetin was able to eradicate pre-prepared S. aureus biofilms at -1 50 mg ml , which completely inhibited biofilm production (87.7%) in a dose-dependent manner. A contemporary study demonstrated the inhibitory effect of quercetin on both clinical and reference -1 isolates of S. aureus (250-500µg ml ) (da Costa Júnior et al, 2018) and another study reported that quercetin crippled biofilm production in S. aureus isolates when applied at various -1 concentrations (1-50 mg ml ) (Kim et al, 2018) which is consistent with our findings. Comparable results show that quercetin also demonstrated reliable antibiofilm activity against S. mutans, which may be used for treating dental caries (Zeng et al, 2019).…”
Section: O N L I N E C O P ÿsupporting
confidence: 92%
“…Quercetin was able to eradicate pre-prepared S. aureus biofilms at -1 50 mg ml , which completely inhibited biofilm production (87.7%) in a dose-dependent manner. A contemporary study demonstrated the inhibitory effect of quercetin on both clinical and reference -1 isolates of S. aureus (250-500µg ml ) (da Costa Júnior et al, 2018) and another study reported that quercetin crippled biofilm production in S. aureus isolates when applied at various -1 concentrations (1-50 mg ml ) (Kim et al, 2018) which is consistent with our findings. Comparable results show that quercetin also demonstrated reliable antibiofilm activity against S. mutans, which may be used for treating dental caries (Zeng et al, 2019).…”
Section: O N L I N E C O P ÿsupporting
confidence: 92%
“…As mentioned above, quercetin and its derivatives more easily disrupt the membrane of gram-positive bacteria compared with that of gram-negative bacteria. In addition, previous studies showed that quercetin and its derivatives inhibit hemolysis and biofilm formation in S. aureus by reducing alpha-toxin secretion [26][27][28][29] , which might explain the S. aureus-specific anti-biofilm effect of di-F-Q. On the other hand, quercetin is also known to inhibit the aqr quorum-sensing system which modules biofilm formation in S. aureus 28 .…”
Section: Resultsmentioning
confidence: 97%
“…The anti-biofilm activities of quercetin in biofilm formation and biofilmrelated infections were also investigated in Streptococcus mutans and Enterococcus faecalis, and results indicated the potential of quercetin in application for antimicrobial infection and anti-caries therapies for human health [50,51]. Furthermore, nanoparticles decorated quercetin and quercetin conjugated microparticles showed more effective anti-biofilm activities [52], opening up a novel approach to develop therapeutic agent in prevention of microbial infections.…”
Section: Quercetinmentioning
confidence: 99%